Electronic Land Certificate for Property Security in Indonesia - Erlinda Risma Yanti; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2025)
The development of computer network technology, including LAN and WAN, has had a significant impact on various aspects of life, including land information services. Land has a strategic role in people's lives, as regulated in Article 33 paragraph (3) of the 1945 Constitution. Good land management can support people's welfare and sustainable investment. The National Land Agency (BPN) as the institution responsible for land affairs has the main task of regulating, serving and administering land. In an effort to increase legal certainty and service efficiency, the government introduced Electronic Land Certificates (STE) based on ATR/BPN Ministerial Regulation No. 1 of 2021. STE offers easy access to information, speeds up land transactions, and increases transparency and accountability. Nonetheless, STE implementation faces challenges, including cybersecurity risks and data inaccuracies. Therefore, a strong security system, clear regulations and public education are needed to ensure the success of STE implementation. With the right strategy, STE can be an innovative solution in modernizing land administration in Indonesia, supporting legal certainty, and improving the quality of public services.